The mediating effects of organisation cultural traits on the relationship between transformational leadership style and corporate members' attitudinal outcomes A study of government-linked companies in Malaysia - Arman Hadi, Abdul Manaf (2012)
This study investigates the relationships between transformational leadership styles, organisational culture and organisational members’ attitudinal outcomes of job satisfaction, organisational commitment and trust in management. Hierarchical multiple regression analysis is used to investigate the relationships between transformational leadership style, the mediating effect of organisational culture and organisational members’ level of job satisfaction, their organisational commitment and trust in their upper management. This study was conducted among corporate members at the managerial levels in the selected Government-linked companies (GLCs) controlled by the GLIC constituents of Putrajaya Committee GLC High Performance (PCG) under the GLC Transformation Programme and the GLCs which are listed in Bursa Malaysia. The results of this study have showed that cultural traits have been positively mediated (fully and partially) the link between transformational leadership styles and corporate members’ attitudinal outcomes. The traits in culture practiced in an organisation through leadership is the main element to design and strategize on the way an organisation works in order to deliver tangible and sustainable results in the future. This study contributes to the dynamics of the causative relations between the selected variables, and highlights the important role of transformational leadership, organisational culture in ascertaining corporate members‘ job satisfaction, organisational commitment and trust in management especially in the Malaysian context.